The Effectiveness of Using Types of Containers and Consentration AB Mix on the Growth and Production of White Packcoy (Brassica rapa L.) Var. Dakota Uses Wick System Hydroponics - Aprilia Hartanti; Retno Sulistyowati (Nabatia, 2022)
The research was conducted in Branggah Village, Lumbang District, Probolinggo Regency, from March to June 2020. This study aimed to determine the effectiveness of using containers and AB mix nutrient concentrations on the growth and production of white pakcoy plants (Brassica Rapa L) using a hydroponic wick system. . The design used was factorial randomized block design (RBD), which consisted of two factors: 1. The wick system hydroponic container material consists of a plastic tub; Styrofoam, Stainless steel 2. Concentration of AB Mix Nutrients consists of 4 (four) levels, namely 1100 ppm; 1300 ppm; 1500 ppm; 1700 ppm with 3 repetitions. Parameters observed: Plant height, number of leaves, plant diameter, plant wet weight, root length, plant dry weight. The results showed that the single treatment of the wick system hydroponic container and the concentration of AB mix showed a significant effect on the observations of plant height, number of leaves, stem diameter, root length, wet and dry weight of plants of all ages of observation. The interaction between container type and nutrient concentration had no effect on all observed parameters except leaf area.